2010
DOI: 10.1111/j.1365-2869.2010.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between symptoms and subtypes of attention-deficit hyperactivity disorder and sleep problems/disorders

Abstract: SUMMAR Y This study aimed to investigate the association between attention-deficit hyperactivity disorder (ADHD) symptoms and subtypes, and sleep schedules, daytime inadvertent napping, and sleep problems ⁄ disorders in children and adolescents with and without ADHD. The sample included 325 patients with ADHD, aged 10-17 years [male: 81.5%; combined type (ADHD-C): 174; predominantly inattentive type (ADHD-I): 130; predominantly hyperactive-impulsive type (ADHD-HI): 21], and 257 children and adolescents without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 51 publications
7
66
1
6
Order By: Relevance
“…Although some authors described more difficulties with morning awakenings (Chiang et al, 2010;Corkum et al, 2001;Owens et al, 2009), others found no support for this (Corkum et al, 1999;Mick et al, 2000;O'Brien et al, 2003a). With regard to daytime parameters, excessive daytime sleepiness has consistently been found to be more common in CIRCADIAN PROFILES IN ADHD 14 children with ADHD compared to normal controls (Chiang et al, 2010;Cortese et al, 2009;O'Brien et al, 2003a;O'Brien et al, 2003b;Owens et al, 2009;Owens et al, 2000). To date, there are few studies of adolescents and adults.…”
Section: <Insertmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some authors described more difficulties with morning awakenings (Chiang et al, 2010;Corkum et al, 2001;Owens et al, 2009), others found no support for this (Corkum et al, 1999;Mick et al, 2000;O'Brien et al, 2003a). With regard to daytime parameters, excessive daytime sleepiness has consistently been found to be more common in CIRCADIAN PROFILES IN ADHD 14 children with ADHD compared to normal controls (Chiang et al, 2010;Cortese et al, 2009;O'Brien et al, 2003a;O'Brien et al, 2003b;Owens et al, 2009;Owens et al, 2000). To date, there are few studies of adolescents and adults.…”
Section: <Insertmentioning
confidence: 99%
“…Cases with ADHD and sleepwake problems and cases with executive function (state regulation) deficit problems would be especially interesting to study. ADHD subgroups may be differentially affected by time of day effects; however, some may show eveningness chronotypology to inattention problems (Caci et al, 2009), whereas others reported the combined group to be more vulnerable for circadian problems (Chiang et al, 2010).…”
Section: Prediction 3: the Association With Circadian Rhythm Is Only mentioning
confidence: 99%
“…Cognitive and motor activity both show circadian variation (Beau, 1992;Weinert and Waterhouse, 1998;Winocur and Hasher, 2004). Moreover, this rhythm is abnormal in the Spontaneously Hypertensive Rat (SHR), the established rodent model of ADHD (Adriani et al, 2003), and in ADHD patients (Chiang et al, 2010). In view of the findings discussed below, it is interesting that L-type Ca 2+ v channels are under circadian control (e.g.…”
Section: Behavioural Deficits Are Attenuated By Repeated Experience Omentioning
confidence: 99%
“…40 Findings [40][41][42][43][44] provide strong evidence to support the relation between ADHD and sleep problems. Studies 40 showed that adolescents with a childhood diagnosis of ADHD, regardless of persistence of ADHD at adolescence or not, were more likely to have various sleep problems such as dyssomnia, sleep-wake pattern disturbance, and breathing-related sleep problems.…”
Section: Psychiatric Comorbidities In Adhd Probandsmentioning
confidence: 99%